THE IMPORTANCE OF BREATHING AND ARTICULATION EXERCISES IN ELIMINATING SPEECH DEFECTS - Maxmudova Madinaxon Sobirxonovna; Abdullayeva Oyjamol Adhamjon qizi (Bright Mind Publishing, 2025)
This article presents the ideas about the importance of breathing and articulation exercises in eliminating speech defects, the inextricable link between speech breathing and the formation of oral speech, its representation of the system of psychomotor reactions, the subordination of the character of speech breathing to intraspeech programming, and the semantic, lexical-grammatical and intonational enrichment of the statement.
Keywords: Respiratory muscles, articulation, respiratory organs, speech breathing, speech exercises, oral speech, pathology, intonation, correction.